Impact of circulating lymphoma cells at diagnosis on outcomes in patients with Waldenstrom macroglobulinemia - Nalin, Ansel; Zhao, Qiuhong; Voorhees, Timothy; Bond, David; Sawalha, Yazeed; Hanel, Walter; Sigmund, Audrey; Annunzio, Kaitlin; Alinari, Lapo; Baiocchi, Robert; Maddocks, Kami; Jones, Dan; et al. (Frontiers in Oncology, 2023)
Given the paucity of data surrounding the prognostic relevance of circulating lymphoma (CL) in Waldenström macroglobulinemia (WM), we sought to evaluate the impact of CL at diagnosis on outcomes in patients with WM. Patients were divided into CL+ and CL-based on the results of flow cytometry. The endpoints included assessing progression-free survival (PFS), overall survival (OS), and diagnosis-to-treatment interval (DTI) between the two groups. Among the 308 patients with WM, 69 met the eligibility criteria with 42 and 27 in CL+ and CL-groups, respectively. The two groups were well balanced in regard to all the baseline characteristics.The ORR was numerically higher in the CL+ group compared to the CL-group (81% versus 61%, respectively), however, the CR+VGPR rates were similar between the two groups. The median PFS was not significantly different between the two groups (6.3 years in the CL-group versus not reached [NR] in the CL+ group) regardless of the first-line therapy. There was no significant difference in median OS between the CL-and CL+ groups (13 years versus NR).Although the median DTI was shorter in the CL+ group compared to CL-group, the significance was lost in the multivariable analysis. In this study (largest-to-date) evaluating the impact of CL on outcomes in patients with newly diagnosed WM, we did not find the prognostic utility of CL in WM. Future studies should explore the correlation of CL with other biological factors that impact the outcomes in WM patients.